2013
DOI: 10.1371/journal.pone.0062379
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Modulation on Perceptual Decision with Balanced Inhibition through Feedforward and Feedback Inhibitory Neurons

Abstract: Recent physiological studies have shown that neurons in various regions of the central nervous systems continuously receive noisy excitatory and inhibitory synaptic inputs in a balanced and covaried fashion. While this balanced synaptic input (BSI) is typically described in terms of maintaining the stability of neural circuits, a number of experimental and theoretical studies have suggested that BSI plays a proactive role in brain functions such as top-down modulation for executive control. Two issues have rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 54 publications
1
33
1
Order By: Relevance
“…Recent studies suggested that, when considering the biological constraints, the attractor-based circuit models out-perform an integrator when accuracy is more important than speed (Miller and Katz 2013), and that robust and optimal decision-making can be realized by neuronal gain modulation in the attractor network model (Niyogi and Wong-Lin 2013). Furthermore, we have shown that the attractor dynamics and the decision behavior of the spiking neural network model can be rapidly changed by a top-down signal with balanced excitation and inhibition Wang et al 2013). This balanced synaptic input (BSI) has been observed in vivo in various nervous systems, including the frontal cortex (Haider et al 2006;Shu et al 2003), primary visual cortex (Mariño et al 2005) and spinal cord (Berg et al 2007).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Recent studies suggested that, when considering the biological constraints, the attractor-based circuit models out-perform an integrator when accuracy is more important than speed (Miller and Katz 2013), and that robust and optimal decision-making can be realized by neuronal gain modulation in the attractor network model (Niyogi and Wong-Lin 2013). Furthermore, we have shown that the attractor dynamics and the decision behavior of the spiking neural network model can be rapidly changed by a top-down signal with balanced excitation and inhibition Wang et al 2013). This balanced synaptic input (BSI) has been observed in vivo in various nervous systems, including the frontal cortex (Haider et al 2006;Shu et al 2003), primary visual cortex (Mariño et al 2005) and spinal cord (Berg et al 2007).…”
mentioning
confidence: 75%
“…Our decision-making model of spiking neurons was described previously (Hsiao and Lo 2013;Lo and Wang 2006;Wang 2002;Wang et al 2013;Wong et al 2007;Wong and Wang 2006) and has been applied to different types of decision processes (Deco et al 2009;Wang 2008). For the sake of concreteness, here we will focus on model simulations of a visual directiondiscrimination task, the random-dot motion task (Roitman and Shadlen 2002).…”
Section: Perceptual Decision-making Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when Cre driver lines became available to separately target gene expression to PV, SST, VIP, or CR neurons (Taniguchi et al 2011), VIP was favored over CR because of the ability to target a population that was separate from PV or SST neurons. Studies of VIP neurons have so far proceeded without concern for the known diversity of VIP cell types, and the grouping of these cells into a monolithic population has appeared to be justified by the striking differences in the connectivity and functional impact of these cells when compared to PV or SST cells (Lee et al 2013;Pfeffer et al 2013). …”
Section: Calretinin (Cr) and Vip-expressing Interneurons Target Sst Imentioning
confidence: 99%
“…Thus, it is apparent that mouse CR bipolar cells preferentially target SST neurons in layer 2/3. In this context, it is not entirely surprising that later studies systematically investigating the connectivity of PV, SST and VIP neurons found strong connections from VIP neurons onto SST neurons in layer 2/3 and not in layer 5 (Lee et al 2013;Pfeffer et al 2013). It remains unclear whether this is a feature of all VIP interneurons or only of the CR-expressing subpopulation.…”
Section: Calretinin (Cr) and Vip-expressing Interneurons Target Sst Imentioning
confidence: 99%